2015
DOI: 10.1016/j.enconman.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Thermal efficiency of coal-fired power plants: From theoretical to practical assessments

Abstract: The improvement in thermal efficiency for coal to power processes is increasingly important due to concerns on CO2 emissions. This paper presents a systematic study on direct combustion coal to power processes with respect to thermodynamic, technical and economic factors. Traditional exergy analysis focuses on irreversibilities in existing processes, while the new methodology investigates the thermal efficiency from its theoretical maximum to practical values by adding irreversibilities one by one. As a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…It is likely to continue as a key component of the fuel mix in the generation of power even though these plants account for over 28% of the total global emissions of carbon dioxide [45]. In order to maximize the utility of coal used in the production of energy, considerable efforts need to be made to enhance the capacity and efficiency of plants whilst simultaneously reducing their environmental impact and costs of power generation [46]. Improving both the efficiency and cost effectiveness of power plants can be achieved by reducing the thermodynamic inefficiencies associated with the system that result in a reduction of the CO 2 emission per MW of electricity generated [47].…”
Section: Coal-fired Heat and Power Plantsmentioning
confidence: 99%
“…It is likely to continue as a key component of the fuel mix in the generation of power even though these plants account for over 28% of the total global emissions of carbon dioxide [45]. In order to maximize the utility of coal used in the production of energy, considerable efforts need to be made to enhance the capacity and efficiency of plants whilst simultaneously reducing their environmental impact and costs of power generation [46]. Improving both the efficiency and cost effectiveness of power plants can be achieved by reducing the thermodynamic inefficiencies associated with the system that result in a reduction of the CO 2 emission per MW of electricity generated [47].…”
Section: Coal-fired Heat and Power Plantsmentioning
confidence: 99%
“…Correlation coefficient (dimensionless) O daf O content of air-dried basis (%) S daf S content of air-dried basis (%) T Thermokinetic temperature (K) T 1 First characteristic temperature, critical temperature (°C) T 2 Second characteristic temperature, active temperature (°C) T 3 Third characteristic temperature, pyrolysis temperature (°C) T 4 Fourth characteristic temperature, ignition temperature (°C) T 5 Fifth characteristic temperature, burned-out temperature (°C)…”
Section: List Of Symbolsmentioning
confidence: 99%
“…China is the largest coal-producing country [3,4], and the problem of coal spontaneous combustion [5][6][7] is gaining increasing attention. To govern the wastage of coal resources, numerous coal mines in China have begun to re-mine old coal mines and mined-out areas, which have a risk of second or multiple oxidations.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that there are considerable opportunities for applying energy conservation measures. Other studies also show the potential for improving the energy efficiency of this type of plants by energy conservation measures . Simulation tools and models of the thermodynamic cycles of steam power plants are useful for predicting and analyzing the cycles' performance by calculating the thermodynamic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also show the potential for improving the energy efficiency of this type of plants by energy conservation measures. [6][7][8] Simulation tools and models of the thermodynamic cycles of steam power plants are useful for predicting and analyzing the cycles' performance by calculating the thermodynamic variables. Therefore, these tools and models can contribute to the running of the plant in a more effective way, since they contribute to an adequate decision making.…”
mentioning
confidence: 99%